2019
DOI: 10.1038/s41598-018-37630-3
|View full text |Cite
|
Sign up to set email alerts
|

Minor sequence modifications in temporin B cause drastic changes in antibacterial potency and selectivity by fundamentally altering membrane activity

Abstract: Antimicrobial peptides (AMPs) are a potential source of new molecules to counter the increase in antimicrobial resistant infections but a better understanding of their properties is required to understand their native function and for effective translation as therapeutics. Details of the mechanism of their interaction with the bacterial plasma membrane are desired since damage or penetration of this structure is considered essential for AMPs activity. Relatively modest modifications to AMPs primary sequence ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 83 publications
4
36
0
Order By: Relevance
“…Temporins are a family of frog-skin AMPs whose various isoforms have already shown activity against Gram-positive bacteria [23,41,42]. For instance, TA has a MIC ranging from 4 to 16 µg/mL towards human methicillin-resistant S. aureus (MRSA) clinical isolates [18]; TB and different synthetic analogs inhibit the growth of various S. aureus strains alone or in combination with TA [22,43]. The cytotoxic TL is noticeably more potent than other temporin peptides in killing S. aureus [44,45] and can act in synergy with TA or TB against Gram-negative bacteria by inducing changes in the biophysical properties of the peptides (e.g., prevention of their oligomeric state) when bound to the lipopolysaccharide [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporins are a family of frog-skin AMPs whose various isoforms have already shown activity against Gram-positive bacteria [23,41,42]. For instance, TA has a MIC ranging from 4 to 16 µg/mL towards human methicillin-resistant S. aureus (MRSA) clinical isolates [18]; TB and different synthetic analogs inhibit the growth of various S. aureus strains alone or in combination with TA [22,43]. The cytotoxic TL is noticeably more potent than other temporin peptides in killing S. aureus [44,45] and can act in synergy with TA or TB against Gram-negative bacteria by inducing changes in the biophysical properties of the peptides (e.g., prevention of their oligomeric state) when bound to the lipopolysaccharide [46].…”
Section: Discussionmentioning
confidence: 99%
“…Temporins were initially isolated from the European red frog Rana temporaria, and nowadays they represent one of the largest groups of amphibian AMPs (more than 100 members) [15,16] and are among the shortest AMPs (only 10-13 residues) present in nature to date. While some isoforms (i.e., temporin A, (TA [FLPLIGRVLSGIL-NH 2 ]); temporin B (TB [LLPIVGNLLKSLL-NH 2 ]); temporin L (TL [FVQWFSKFLGRIL-NH 2 ]) of this family have already been characterized for their antimicrobial and cytotoxic properties [16][17][18][19][20][21][22][23][24], very little is known about the antimicrobial potential of temporin G (TG [FFPVIGRILNGIL-NH 2 ]) [25], which was isolated from the same frog specimen, especially against the bacterial biofilm phenotype. To the best of our knowledge, this is the first manuscript describing TG activity against preformed S. aureus biofilm as well as against persister cells.…”
Section: Introductionmentioning
confidence: 99%
“…TB_L1FK (Table 1) is a computationally designed analog of TB that contains a replacement of Leu1 to Phe, the deletion of residue Asn at position 7, and an addition of Lys13 at the C-terminus. Studies comparing the antibacterial activity of TB_KKG6A and TB_L1KF [109,110] showed that both analogs showed higher MIC values of 32 to 64 μM, against most of the Gram negative strains tested; however, Figure 1. Structures of (A) the TL dimer; (B) TA; and, (C) TB in LPS.…”
Section: Sequence Net Chargementioning
confidence: 98%
“…Unlike most antibiotics that may lose activity if their basic structure is modified, AMPs are particularly prone to molecular alteration. They can be optimized by altering their primary sequence through the incorporation or deletion of hydrophobic or charged amino acids, which has been shown to affect their selectivity for Gram-positive, Gram-negative or fungal membranes [ 113 , 114 , 115 , 116 ]. The killing of specific pathogens within a mixed bacterial population has been achieved in vitro by AMPs, referred to as specifically targeted antimicrobial peptides (STAMPs).…”
Section: Single- or Multiple-targeted Amps To Discriminate Pathogementioning
confidence: 99%